Detecting suicide risk in psychiatric emergency services - Bertolote, José Manoel [UNESP]; Santos, Carolina de Mello [UNESP]; Botega, Neury José (EDITORA SCIENTIFIC, 2010)
Objective: To provide guidelines for the identification of suicide risk and protective factors and the management of suicidal patients in emergency settings. Method: Literature review to identify relevant and illustrative key cases. Results: The clinical interview is the best method to evaluate the suicidal risk and has a twofold purpose: 1) providing emotional support and creating a bond; 2) collecting information. There is a substantial amount of information to be collected during the clinical interview, including risk and protective factors, epidemiologic data, characterization of the event, psychodynamic aspects, personal and family history, identification models, data on physical health, and social support network. Difficulties can emerge during the clinical interview, but a trained and informed professional will be able to approach and adequately deal with the patient. Although several scales have been proposed, none of them have shown reliable efficiency in determining the suicidal risk. Conclusion: There is no method to predict who is going to commit suicide; nevertheless, it is possible to evaluate the individual risk of each patient by means of a detailed and empathic clinical interview. Keeping the patient alive is the first and fundamental rule.

Objetivo: Auxiliar o profissional de saúde na identificação dos fatores de risco e de proteção, e no manejo de pacientes com risco de suicídio, por meio de entrevista clinica, no contexto de emergência médica. Método: Revisão seletiva da literatura para identificar achados clínicos relevantes e ilustrativos. Resultados: A entrevista clinica é o melhor método para avaliar o risco suicida e tem dois objetivos: 1) apoio emocional e de estabelecimento de vínculo; 2) coleta de informações. Existe um número considerável de informações a serem coletadas durante a entrevista: fatores de risco e proteção (predisponentes e precipitantes), dados epidemiológicos, caracterização do ato, aspectos psicodinâmicos, antecedentes pessoais e familiares, modelos de identificação, dados sobre saúde física e rede de apoio social. Dificuldades ao longo da entrevista serão encontradas, mas com conhecimento e treinamento adequado, o profissional poderá abordar e ajudar adequadamente o paciente. Embora várias escalas tenham sido propostas, nenhuma delas demonstrou eficiência para a detecção de risco de suicídio. Conclusão: Não há como prever quem cometerá suicídio, mas é possível avaliar o risco individual que cada paciente apresenta, tendo em vista a investigação detalhada e empática da entrevista clinica. Impedir que o paciente venha a se matar é regra preliminar e fundamental.
Detecção do risco de suicídio nos serviços de emergência psiquiátrica
Keywords: Suicide; Emergency services; Psychiatric; Interview; Risk factors; Protection; Suicídio; Serviço de emergência psiquiátrica; Entrevista; Fatores de risco; Proteção